Proposed Marketing Strategy for Prima Rasa Bakery and Pastry - Stephanie, Hanna Friska; Wibowo, Satya A (The Indonesian Journal of Business Administration, 2014)
Abstract. Prima Rasa Bakery and Pastry is a family owned bakery and pastry shop which located in Bandung, Indonesia. Â The bakery was established in 1986 by Theresia Yuliaty . The company is working in food retailers, bakers business activities. It is selling a wide variety of cake, bread, and snack. Research conducted from the internal and external analysisÂ  and brand equity of Prima Rasa Bakery and Pastry. Internal analysis conducted by performing analysis on Segmenting, Targeting, Positioning (STP) and Marketing Mix (7P) and external analysis by conducted 5Câ€™s of Prima Rasa Bakery and Pastryâ€™s business environment. While brand equity is performed by analyzing Brand Awareness, Brand Loyalty, Brand Association, and the Perceived Quality. However old players competitor such as Kartika Sari, Mayasari and etc has already established great brand recognition as the â€œtrademark souvenir bakery of Bandungâ€ especially among customers from outside Bandung and some of them also has more bakery stores in Bandung and offer delivery service to customers outside the city.Root causes obtained from this research were the service was less optimized and the company does not focus on the right target market eventhough the industryâ€™s comptitiveness is keep increasing. Therefore by conducting the clustering analysis method to choose the right target market for Prima Rasa Bakery and Pastry and also using the right approach for the marketing strategy implementation.In performing the marketing strategy activities, Prima Rasa Bakery and Pastry should emphasize the primary targets that focus on quality, price, and services. The most effective promotion is through Official Website, Social Media, and Catalogue, also considered to increase the product awareness. Beside the promotion, Prima Rasa Bakery and Pastry should also give discount, bonus, and offer seasonal event product to the customers. Training for the employee is vital to provide the better services for the customer.Â Key Words:Â  Prima Rasa Bakery and Pastry, Brand Equity, Marketing Mix